Die Rolle von Ceramiden und assoziierten Faktoren in der Bildung von Coronavirus-induzierten replikativen Organellen - Salisch, Florian; Justus Liebig University Giessen (My University, 2025)
RNA viruses have evolved diverse strategies to re-program and exploit host cellular functions and molecules, including cellular lipids, to ensure efficient virus replication and production of infectious virus progeny. A conserved feature of plus-strand RNA virus replication is the formation of membranous microenvironments (replicative organelles, ROs) in virus-infected cells. RO formation is known to be initiated by virus-encoded membrane-associated nonstructural proteins and involves extensive remodeling of host cell membranes. This process is thought to involve cellular enzymes responsible for synthesizing and modifying specific lipids. In this study, I investigated the potential roles of specific cellular sphingolipids and enzymes acting on sphingolipids in the replication of different coronaviruses. The data revealed that, following infection, cellular ceramide species increase significantly, whereas sphingomyelin levels decreased, indicating an involvement of sphingomyelinases that convert sphingomyelin to ceramide. To verify this, I targeted the cellular sphingomyelinases using pharmacological and genetic approaches. I could provide evidence that neutral sphingomyelinase 2 (nSMase2) plays an essential role in an early phase (but not entry) of coronavirus replication in Huh-7-ACE2 cells. Furthermore, I was able to demonstrate a colocalization of neutral sphingomyelinase 2 and ceramide, but not sphingomyelin, with both infection-induced and genetically induced ROs. Ceramides and coronaviral ROs were found to colocalize in different cell systems used in this study. However, in another set of experiments, I also obtained data to suggest that the extent of specific sphingolipid deregulations and the role of nSMase2 in coronavirus infections may vary among different infection systems, depending on the cell type used. Taken together, this study strongly suggests that ceramides serve as crucial lipid building blocks in the formation of coronaviral ROs in different cell types, suggesting that inhibition of cellular ceramide production may represent a potential antiviral strategy against coronavirus infections. However, the mechanisms of ceramide generation or recruitment to specific intracellular sites seem to vary depending on the cell type used and, possibly, the baseline ceramide levels in these cell types. Further investigation is required to clarify these variations and their biological implications.
Keywords: ddc:570; ddc:610